Exploring the Relationship Between Regulatory Compliance, Internal Control, Managerial Competence, and Financial Integrity of Indonesian Start-Ups - Chatra, Afdhal (Sinergi International Journal of Accounting and Taxation, 2023)
This study examines the relationship between regulatory compliance, internal control, management competence, and financial integrity to better understand the dynamics that influence the resilience and performance of Indonesian startups. Our quantitative research uses Structural Equation Modeling with Partial Least Squares (SEM-PLS 4) and is based on a stratified random sample of 215 startups from different industries, sizes, and countries. Strong validity and reliability are demonstrated by the measurement model, and good correlations between important constructs are highlighted by the path coefficients. The beneficial effect of regulatory compliance on financial integrity is shown to be amplified by internal control, which is found to be a key mediator. The validity of the suggested relationships is reinforced by the good fit of the structural model. The results of this study provide insightful information for academics, politicians, and startup executives, and offer solutions to navigate the complicated terrain of the startup ecosystem in Indonesia. The results of this study provide useful information for policymakers and startup executives. Maintaining financial integrity requires strengthening internal controls, especially when combined with an emphasis on managerial competence. A customised approach considering industry, scale, and local environment can improve overall financial health and regulatory compliance